PUBLIC – PRIVATE PARTNERSHIP IN THE FUNCTION OF SUSTAINABLE BUSINESS OF ECONOMIC ENTITIES IN AGRICULTURE - Miletić, Vesna; Rajnović, Ljiljana Dušan; Jovičić, Aleksandar (Economics of Agriculture, 2024)
In the global competition in agriculture, countries must allocate considerable financial resources in order to create preconditions for the continuous development of agriculture. Bearing in mind the unfavorable competitive position, the low investment rating, insufficient foreign direct investments, the Republic of Serbia can see its development opportunity in the application of public-private partnership in agriculture. Cooperation models are conditioned by investor plans and regulations created by the state. The mutually significant and complex relationship between the private and public partner beside economic and legal aspects, also acquires significant social and political dimensions. That is why through public-private partnership operations, there is an opportunity to improve the operations of economic entities. The authors conducted a survey of business entities in the territory of Srem, analyzed a successful case and concluded that the mentioned partnership can lead to an improvement in the competitiveness of business entities in the field of agriculture.